Addressing Challenges in Formal Research on Moribund Heritage Languages: A Path Forward - D'Alessandro, Roberta; Natvig, David; Putnam, Michael T. (Frontiers in Psychology, 2021)
The substantial uptick in research on heritage languages over the past three decades has enhanced our understanding of the development of bilingual grammars throughout the lifespan. This interest has been accompanied by a noticeable increase of experimental work, often combined with some degree of formal rigor. Exclusively and predominantly formal research on these languages – especially studies whose empirical focus centers on moribund heritage varieties – occasionally encounters criticism, due primarily to a lack of understanding of the methodology and objectives of this body of research as a whole. The purpose of this positional essay is to once again elucidate with clarity the motivation and importance of formal linguistic research on these languages, providing a fruitful path forward for continued work in this well-established field of linguistic inquiry.